2018
DOI: 10.1371/journal.pone.0202212
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome composition within a sympatric species complex of intertidal isopods (Jaera albifrons)

Abstract: The increasingly recognised effects of microbiomes on the eco-evolutionary dynamics of their hosts are promoting a view of the “hologenome” as an integral host-symbiont evolutionary entity. For example, sex-ratio distorting reproductive parasites such as Wolbachia are well-studied pivotal drivers of invertebrate reproductive processes, and more recent work is highlighting novel effects of microbiome assemblages on host mating behaviour and developmental incompatibilities that underpin or reinforce reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 97 publications
2
17
1
Order By: Relevance
“…We conclude that Wolbachia bacteria are present in at least two species of the Jaera albifrons complex in French regions Brittany and Normandy, but most likely with a very small prevalence (both in terms of the number of individuals infected and the concentration of bacteria within infected individuals). This finding consolidates the simultaneous result obtained by Wenzel et al (2018), where bacterial 16s rDNA sequencing did not reveal any trace of Wolbachia in Scottish populations from the four European species of the Jaera albifrons complex.…”
Section: Praehirsutasupporting
confidence: 90%
See 2 more Smart Citations
“…We conclude that Wolbachia bacteria are present in at least two species of the Jaera albifrons complex in French regions Brittany and Normandy, but most likely with a very small prevalence (both in terms of the number of individuals infected and the concentration of bacteria within infected individuals). This finding consolidates the simultaneous result obtained by Wenzel et al (2018), where bacterial 16s rDNA sequencing did not reveal any trace of Wolbachia in Scottish populations from the four European species of the Jaera albifrons complex.…”
Section: Praehirsutasupporting
confidence: 90%
“…Other endosymbiotic manipulators of sex (such as bacteria from groups Cardinium, Rickettsia, and Spiroplasma, or microsporidia) could be involved. In their microbiome study, (Wenzel et al, 2018) found evidence for the presence of Rickettsiacea in J. ischiosetosa females (and not in males), but in minute quantities (1.16% of the 16s sequences obtained for a sample of J. ischiosetosa females, M. Wenzel pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found high bacterial diversity both in the environmental and host microbiomes, 12,566 OTUs in total. Diverse bacterial communities are associated with other marine invertebrates (Moisander et al, 2015 ; Weigel & Erwin, 2017 ; Wenzel et al, 2018 ), and this may reflect the vast diversity of marine bacteria in general (Glöckner et al, 2012 ). In the environmental samples the dominant phyla were Proteobacteria and Bacteroidetes, which is typical for marine environment (Bolhuis & Cretoiu, 2016 ; Gilbert et al, 2009 ; Wenzel et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the increase in temperature leads to the loss of bacteria belonging to Actinobacteria in the common rough woodlouse Porcellio scaber [ 26 ]. In sympatric populations of the marine isopod Jaera albifrons the variance in the microbiota composition over a year was mainly explained by the season and to a lesser extent by sex and geographical origin [ 27 ]. The composition of the digestive microbiota of P. scaber is significantly affected by the host diet in particular by the amount of biofilms it ingests [ 28 ].…”
Section: Introductionmentioning
confidence: 99%